A SPOKESPERSON IN THE DIGITAL AGE: TRANSFORMATION, CHALLENGES AND OPPORTUNITIES - Nadiia Bilan; Vitalii Kornieiev; Margaryta Netreba (Інтегровані комунікації)
The study aims to explore the transformation of the role of the spokesperson in the digital age due to the expansion of the spokesperson’s scope of activities as a result of personal interaction with the public, the need to manage modern digital platforms, ensure consistency of messages and adapt to the new format and speed of news dissemination.